Co-carriage of diverse vancomycin-resistant Enterococcus faecium ST80-lineages by 70% of patients in an Irish hospital - Coleman, David; Kinnevey, Peter (My University, 2025)
Background: Vancomycin-resistant Enterococcus faecium (VREfm) are significant nosocomial pathogens. Irish VREfm comprise diverse vanA-encoding ST80-complex type (CT) lineages. Recent studies indicate that within-patient VREfm diversity could confound surveillance. This study investigated the intra-host VREfm genetic diversity among colonized Irish hospital patients. Methods: Rectal VREfm (n = 150) from 10 patients (15 isolates each) were investigated by WGS, core-genome MLST and split k-mer (SKA)-SNP analysis. Plasmids and vanA-transposons from 39 VREfm representative of CTs identified were resolved by hybrid assembly of short-read (Illumina) and long-read (Oxford Nanopore Technologies) sequences. Plasmid relatedness was assessed based on Mash distances. Thirty vancomycin-susceptible E. faecium (VSEfm) from four VREfm-positive patients were also investigated. Results: All isolates were clade A1 and most were ST80 (VREfm, 147/150; VSEfm, 25/30). Seventy-percent of patients (7/10) harboured either two (n = 4), three (n = 2) or four (n = 1) VREfm CTs. Individual patient isolate pairs from different CTs differed significantly (median SKA-SNPs 2933), but differences were minimal between isolate pairs of the same CT (median SKA-SNPs 0). In total, 193 plasmids were identified in 39 VREfm investigated. Near-identical plasmids (≥99.5% average nucleotide identity) were identified in divergent CTs from multiple patients. Most VREfm (28/39, 72%) harboured vanA on closely related transferable, linear plasmids. Divergent CTs within individual patients harboured either indistinguishable vanA-transposons or vanA-transposons with distinct organizational iterations. Four VSEfm from different CTs investigated harboured similar plasmids to VREfm. Conclusion: VREfm within-host diversity is highly prevalent in Irish hospital patients, which complicates surveillance. Linear plasmids play an important role in the emergence of Irish VREfm.
Keywords: Genes & Society; Immunology, Inflammation & Infection; Drug Resistance; Genetic/Molecular epidemiology; Genomes, Genomics; Infectious diseases; Molecular Biology; Chronic Health Condition; Health